Working with Students to Decolonise the Study of Crime - Sanaz Zolghadriha; Amy Thornton; Jawaher Magnaye (Education Sciences, 2025)
Recent years have seen a fluctuation in the awarding gap between white and non-white students across higher education in the UK, with the most recent numbers indicating a widening of the gap. Such statistics have ignited efforts across universities to identify possible explanations and solutions to the existing awarding gap. With research pointing to the important role of students’ sense of belonging in the positive university experiences of students from minority ethnicities, initiatives have focused on increasing this sense of belonging through curriculum design and delivery. Namely, institutions are moving towards decolonising, or liberating, existing curricula to facilitate an inclusive educational culture. Leaning on success stories from previous projects, this paper presents a case study of working with students to decolonise the curriculum of crime science at University College London. The paper presents the customisation of the UCL Inclusive Curriculum Health Check, a review of the curriculum of BSc Crime and Security Science, and a heatmap and descriptive results of the indicators of an inclusive curriculum. The outcome of the study illustrates the importance of working with students to dismantle colonial narratives in existing curriculum design, and the added value of customising existing frameworks to fit discipline needs. The results and outcome of the project are discussed in relation to the prior literature, and considerations of future directions and limitations of the study are offered.